Evaluation of the Effects and Risks of Cost Estimation on Project Costs and Claims: A Study in Imo State, Nigeria - Ejekwu B. Tobechi; Ekweani P. Chioma; Oha J. Ezinne (Three E Science Institute, 2022)
The construction industry is challenged with project risks often resulting from cost estimating uncertainties. Previous research shows that 50% of construction disputes are estimating-risk related, leading to poor project performance. This study investigated the effects of charge evaluating risks on project cost overrun and resultant claims to improve project efficiency. The investigation was carried out using well-structured questionnaires addressed to construction professionals in Imo state to determine the critical cost estimating risks and identify principal evaluating risk-related claims contributing to cost overrun in construction project delivery. The results reveal that design issues (design complexity, preliminary design, and design errors) are the key contributors to cost estimating uncertainties. Inadequate cost data, estimator's expertise, and omission in contract documents are the principal causes of evaluating risk-related claims in construction projects. The study concluded that the inaccurate estimation of construction costs eventually leads to claims and cost overruns in the delivery of building projects. It's possible that the risk involved in cost evaluation is to blame for this. Estimators with sufficient efficiency, skill, and experience should be included in estimating to increase the likelihood that the estimates will be close to correct. The study recommends the availability of concise designs and specifications and details as well as updated market surveys to eliminate uncertainties and improve cost data before estimating a construction project.